Management Concept of Islamic Higher Education and The Challenge in Global Era - Ahmad Bahrowi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Management is a process of managing Islamic higher educaton institutions by taking into account the vison and mission and how to handle learning resources, methods and strategies as well as other matters relating to the achievement of educational goals effectively and effiecently. The purpose of this study is to solve the problems and challenges of Islamic higher education, especially at the level of management concepts of planning, organizing, and controlling or supervising. This research uses a qualitative research type with an analytical-descriptive approach, namely by analyzing related documents in accordance with the variables in the research or what is commonly called library research. Against the formulation and the goal of this research is to solve the problems and challanges of Islamic higher education especially at the concept level of Islamic education planning management concept is required; planning, organizing and controlling or supervising. Associated with madrasah concentration, it is necessary to have a clear concept of madrasah education planning, learning planning, the importance of lesson planning, improvement of learning quality, learning is designed with system approach, instructional design refers to how people learn, on individual students, on purpose, at ease of learning and involves learning variables toward the goal.